Implementation of STEAM in Schools in Timor-Leste: Challenges and Opportunities - De Deus, João Mariano Helder (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
Education is evolving rapidly to keep pace with a world increasingly driven by technology. Traditional teaching methods often fail to adequately prepare students for today’s challenges. This study looks at STEAM education, which brings together Science, Technology, Engineering, Arts, and Math, and how it can help students in Timor-Leste develop important skills like critical thinking, creativity, teamwork, and flexibility. Using a review of existing data, including national policies, reports from international organizations, and successful examples from countries like Finland and Singapore, the study examines key areas such as curriculum, teacher training, school resources, digital tools, and policy support. The results show that STEAM education can make learning more engaging and effective, but Timor-Leste faces problems like limited resources, not enough trained teachers, and no clear national plan for STEAM. To improve this, the study suggests a careful, step-by-step approach that fits Timor-Leste’s needs and supports fair and lasting changes in education